Cross‐sectional serum metabolomic study of multiple forms of muscular dystrophy. Issue 4 (14th February 2018) - Spitali, Pietro; Hettne, Kristina; Tsonaka, Roula; Sabir, Ekrem; Seyer, Alexandre; Hemerik, Jesse B.A.; Goeman, Jelle J.; Picillo, Esther; Ergoli, Manuela; Politano, Luisa; Aartsma‐Rus, Annemieke
Abstract: Muscular dystrophies are characterized by a progressive loss of muscle tissue and/or muscle function. While metabolic alterations have been described in patients'‐derived muscle biopsies, non‐invasive readouts able to describe these alterations are needed in order to objectively monitor muscle condition and response to treatment targeting metabolic abnormalities. We used a metabolomic approach to study metabolites concentration in serum of patients affected by multiple forms of muscular dystrophy such as Duchenne and Becker muscular dystrophies, limb‐girdle muscular dystrophies type 2A and 2B, myotonic dystrophy type 1 and facioscapulohumeral muscular dystrophy. We show that 15 metabolites involved in energy production, amino acid metabolism, testosterone metabolism and response to treatment with glucocorticoids were differentially expressed between healthy controls and Duchenne patients. Five metabolites were also able to discriminate other forms of muscular dystrophy. In particular, creatinine and the creatine/creatinine ratio were significantly associated with Duchenne patients performance as assessed by the 6‐minute walk test and north star ambulatory assessment. The obtained results provide evidence that metabolomics analysis of serum samples can provide useful information regarding muscle condition and response to treatment, such as to glucocorticoids treatment.